Genetic relationships among breeding soundness traits in yearling bulls - R.A. Christmas; M.F. Spire; J.M. Sargeant; Sharon K. Tucker; Daniel W. Moser (Kansas Agricultural Experiment Station Research Reports, 2001)
Breeding soundness examination data on over 1,200 yearling Angus bulls were analyzed to determine heritability of and genetic relationships among breeding soundness traits. Breeding soundness exam procedures were consistent with those currently recommended by the Society of Theriogenology. Presence of seminal white blood cells (an indicator of seminal vesiculitis), penile warts and persistent frenulums were noted and recorded. Data were adjusted for age at measurement and contemporary group effects. Heritability was high for scrotal circumference, moderate for percentage of abnormalities, low for sperm motility, and near zero for semen white blood cells, persistent frenulum, and penile warts. Genetic correlations between scrotal circumference and both sperm motility and abnormalities were favorable, indicating that selection for increased scrotal circumference should result in higher fertility.
Keywords: Cattlemen' s Day; 2001; Kansas Agricultural Experiment Station contribution; no. 01-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 873; Beef; Bulls; Breeding soundness exam; Heritability; Genetic correlation; Scrotal circumference